Application of High-Resolution Melting (HRM) Technique Towards the Detection of Asymptomatic Malaria in a Malaria Endemic Area of Southeastern Iran Under Elimination Program - Francan Felix Ouma; Mehdi Nateghpour; Afsaneh Motevalli Haghi; Mehdi Mohebali; Leila Farivar; Ahmad Hosseini-Safa; Sayed Hussain Mosawi (Tehran University of Medical Sciences, 2021)
Background: Asymptomatic malaria, which usually exists in low parasitemia, acts as the Plasmodium species reservoirs contributing towards malaria transmission. This situation hinders malaria elimination programs in endemic areas, thus necessitating an active case detection with a high sensitive method and treatment of cases. This is why we used a High Resolution Melting (HRM) assay to monitor the trend of asymptomatic malaria in a malaria endemic area of Iran which is under elimination program. Methods: The peripheral blood was sampled from 271 clinically approved non-febrile individuals from a malaria endemic zone of southeastern Iran for asymptomatic malaria prevalence detection by microscopy, Rapid Diagnostic Tests (RDTs) and HRM methods. The HRM assay was done based on the amplification of 18S SSU rRNA gene. Results: The HRM assay revealed infections from three individuals out of 271 (1.1% asymptomatic malaria prevalence) from the participants, two Iranian natives with Plasmodium vivax infection and one Pakistani immigrant with P. falciparum infection. Neither microscopy nor RDTs detected Plasmodium spp infections from the 271 non-febrile individuals. The nucleotide sequencing analysis of the positive controls used in this study showed a close homology with the reference gene bank sequences of P. falciparum 3D7 (CPO16995.1) and P. vivax Sal-1(UO3079.1). Conclusion: This study revealed a low frequency of asymptomatic malaria trend within malaria endemic areas of southeastern Iran which are under intense elimination program and also the ability of HRM assay in detecting low Plasmodium spp parasitemia beyond the limits of microscopy and RDTs.